Involvement and burden of informal caregivers of patients with mental illness: the mediating role of affiliated stigma - Kaggwa, Mark Mohan; Najjuka, Sarah Maria; Mamun, Mohammed A.; Griffiths, Mark D.; Nyemara, Novatus; Ashaba, Scholastic (BMC psychiatry, 2023)
Background: The fear and lack of understanding of mental illness can lead to stigma. The stigma of mental illness affects not only individuals who suffer from it, but also the caregivers. Stigma among caregivers can lead to delay in seeking care, poor adherence to treatment and a high risk of relapse. Caregivers of patients with mental illness are at an increased risk of distress due to the burden to stigma and caregiving burden. An increase in caregivers’ burden can lead to a reduction in caregivers’ involvement. There is a relationship between caregivers’ involvement, burden, and affiliated stigma. The present study examined the mediating role of affiliated stigma in the relationship between caregivers’ burden and involvement among informal caregivers of hospital-admitted patients with mental illness in Uganda. Methods: A cross-sectional study was conducted among 428 informal caregivers (mean age: 39.6 years [SD±14.6]; females = 62.1%). Information was collected regarding sociodemographic characteristics, affiliated stigma, and the involvement and burden of informal caregivers. Results: The findings indicate that affiliated stigma serves as a full mediator between the caregiver’s roles and involvement (β=15.97, p<0.001). Being female increased the caregivers’ burden of caregiving (β= -0.23, p<0.001). Conclusion: The findings in the present study suggest that intervention to address affiliated stigma among caregivers of patients with mental illness should be incorporated into mainstream mental health care to reduce the caregiving burden.
Keywords: Affiliated stigma; Informal caregivers; Mental illness; Marital status; Caregivers’ burden; Caregivers’ involvement